2020
DOI: 10.7150/ijms.46530
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative BMI Loss at One Year Correlated with Poor Outcomes in Chinese Gastric Cancer Patients

Abstract: Purpose: The present study focused on the long-term prognostic value of dynamic body mass index (BMI) change in gastric cancer patients who underwent gastrectomy. Methods: Clinical data from a total of 576 gastric cancer patients who underwent radical gastrectomy were collected. Univariate and multivariate analyses were performed to demonstrate the association between dynamic BMI variables (BMI before surgery, 1 month, 6 months or 12 months after surgery) and prognosis (DFS and OS). The correlation between BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In our study, BMI, prealbumin, and PNI represented patients' nutritional status, and NLR, PLR, and LMR represented patients' immune-inflammatory microenvironment. Interestingly, in line with our previous study and other researches (15,21), high-BMI patients showed better prognosis, which further confirmed a phenomenon called the "obesity paradox" in the prognosis of GC. Cancer-associated malnutrition also contributes to severe postoperative complications, decreased immunological function, and the activation of the systemic inflammatory response (SIR), leading to poor therapeutic efficacy (7,22).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, BMI, prealbumin, and PNI represented patients' nutritional status, and NLR, PLR, and LMR represented patients' immune-inflammatory microenvironment. Interestingly, in line with our previous study and other researches (15,21), high-BMI patients showed better prognosis, which further confirmed a phenomenon called the "obesity paradox" in the prognosis of GC. Cancer-associated malnutrition also contributes to severe postoperative complications, decreased immunological function, and the activation of the systemic inflammatory response (SIR), leading to poor therapeutic efficacy (7,22).…”
Section: Discussionsupporting
confidence: 90%
“…The continuous variables (normal value), including CA12-5 (35 U/ml), CA19-9 (35 U/ml), CEA (5 ng/ml), AFP (8.78 ng/ml), hemoglobin (120 g/L), total protein (60 g/L), prealbumin (180 mg/L), albumin (35 g/L), albumin-globulin ratio (AGR, 1.25), neutrophil count (7×10 9 /L), lymphocyte count (0.8×10 9 /L), monocyte count (1×10 9 /L), and platelet count (320×10 9 /L), were grouped according to the standards developed by the clinical laboratory of Ruijin Hospital. The optimal cut-off of preoperative BMI(23 kg/m 2 ) was determined by Asian-specific criteria based on our previous study ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with our study, in a large study conducted in Chinese population to dynamically monitor the association between postoperative BMI and prognosis in GC patients, BMI loss of more than 10% within the first year after surgery was found to be associated with poor prognosis. 23 We speculate that BMI is more reflective of changes in the nutritional status of the body in the early postoperative period.…”
Section: Discussionmentioning
confidence: 88%
“…Subgroup analysis was performed by age (<60 and≥60 years), BMI (<23 and≥23 kg/m 2 ) and ALT (<40 and≥40U/L). Specifically, age≥60 years was defined as “older” and <60 years as “young-middle-aged” ( 18 ); BMI≥23kg/m 2 was defined as “overweight/obese” and <23kg/m 2 as “normal/underweight” according to Asian-specific criteria ( 19 ); ALT≥40U/L was defined as “elevated” and <40U/L as “normal” ( 20 ). In addition, lipid profiles were grouped into quartiles as continuous variables.…”
Section: Methodsmentioning
confidence: 99%